Success story of an organic farmer from Khargone District of Madhya Pradesh - Patidar, Lakhan (Indian Farming, 2024)
In the declaration of COP28 UAE on Sustainable Agriculture, Resilient Food Systems and Climate Action, the focus was on the conservation, protection and restoration of land and natural ecosystems. Sustainable and healthy agriculture can play a major role in solving the problem of global hunger and effective management of natural resources. In this article, the success story of an organic farmer, Mr. Rameshwar Bariya, who is from a very small village – Awalya, in Khargone district of Madhya Pradesh in Central India has been described. Farmers like Rameshwar Bariya can be the game changer to promote the adoption of sustainable farming practices. The article details the journey of the farmer from conventional to sustainable farming and his experiences of adopting different organic farming practices. The article also highlights the impact of Narmada Landscape Restoration Project, a unique project funded by United States Agency of International Development (USAID) and NTPC Ltd., and jointly implemented by Global Green Growth Institute (GGGI) and Indian Institute of Forest Management (IIFM) towards the movement for sustainable agriculture and ecosystem of the region.